Evaluation of Routine Enteric Pathogens in Hospitalized Patients: A Canadian Perspective - Kevin Gough; Michelle Alfa; Godfrey Harding (Canadian Journal of Infectious Diseases)
Diarrhea is a frequently encountered problem in hospitalized patients. Since nosocomial spread of routine enteric pathogens such as Salmonella species, Shigella species, Campylobacter species and Escherichia coli O:157 H:7 seldom occurs, testing for these organisms in patients hospitalized for longer than three days has been questioned. The goal of this study was to determine the length of hospitalization preceding detection of routine enteric pathogens and Clostridium difficile cytotoxin, and to develop guidelines for enteric cultures from hospitalized patients. The enteric pathogens detected in 1991 were C difficile toxin B(+), 77%; Campylobacter species, 10%; Salmonella species, 9%; E coli O:157 H:7, 3%; and Shigella species, 1%. For 1992, these numbers were 86%, 9%, 3%, 2% and 0%, respectively. None of the routine enteric pathogens isolated in 1991 or 1992 was detected in patients after their second day of hospitalization. Routine cultures for enteric pathogens on hospitalized patients were eliminated in February 1993, and physician ordering practices were monitored. With the exception of one campylobacter isolate per year, all routine enteric pathogens isolated in 1993 and 1994 were detected by the second day of hospitalization. Compliance with the changed protocol was 76% measured over a four-month period in 1993 and 74% over the year 1994. Savings of $3,648.10 were associated with rejecting 191 ‘inappropriate’ specimens in 1994. It was concluded that routine enteric cultures are unnecessary for patients hospitalized more than two days, and that appreciable financial savings can be achieved if revised protocols for processing stool cultures are instituted. However, when enteric protocol changes are in place compliance must be evaluated to ensure appropriate utilization.